Calcium‐Based Metal–Organic Frameworks and Their Potential Applications. Issue 22 (3rd November 2020) - Xian, Shikai; Lin, Yuhan; Wang, Hao; Li, Jing
Abstract: Metal–organic frameworks (MOFs) built on calcium metal (Ca‐MOFs) represent a unique subclass of MOFs featuring high stability, low toxicity, and relatively low density. Ca‐MOFs show considerable potential for molecular separations, electronic, magnetic, and biomedical applications, although they are not investigated as extensively as transition metal‐based MOFs. Compared to MOFs made of other groups of metals, Ca‐MOFs may be particularly advantageous for certain applications such as adsorption and storage of light molecules because of their gravimetric benefit, and drug delivery due to their high biocompatibility. This review intends to provide an overview on the recent development of Ca‐MOFs, including their synthesis, crystal structures, important properties, and related applications. Various synthetic methods and techniques, types of building blocks, structure and porosity features, selected physical properties, and potential uses will be discussed and summarized. Representative examples will be illustrated for each type of important applications with a focus on their structure–property relations. Abstract : Metal–organic frameworks built on calcium (Ca‐MOFs) represent an important subgroup of MOFs. They possess diverse structures, low toxicity, and light weight, and hold promise for a variety of applications. An overview on Ca‐MOFs reported to date, including a summary of inorganic building units, organic ligands, crystal structures, porosity, and selected physical properties, as well as most promising applications is offered.